Flexible "parts" and rigid "fulls" the limited revolution in work-time patterns - Dey, Ian (1989)
The evidence indicates that there has been some erosion of the distinction between part-time and full-time employment over the past decade. However, this is almost entirely attributable to the growth in part-time employment, and despite a continuing rigidity in full-time work patterns. It is argued that part-time employment can only make a limited contribution to labour market flexibility so long as full-time work patterns remain inflexible. This paper questions the assumptions sustaining a rigid bifurcation of work into full-time and part-time hours, and considers the case for a more flexible approach to full-time hours in the context of the debate over worksharing.